Pengaruh Durasi Pemanasan Aspal dan Simulasi Penuaan Campuran Aspal terhadap Kinerja Stiffness, Creep, dan Fatigue Perkerasan Jalan - I Gusti Agung Bagus Chandrastika Wangsa; I Made Agus Ariawan; I Nyoman Arya Thanaya (Jurnal Konstruksi, 2025)
This study aims to analyze the effect of asphalt heating duration and asphalt mixture aging simulation on the performance of stiffness, creep, and fatigue of road pavements. The research was conducted experimentally, with samples obtained from 30 asphalt core drillings in the field, each subjected to six treatments consisting of V1 (1 hour), V2 (2 hours), V3 (3 hours), V4 (6 hours), V5 (7 hours), and V6 (8 hours), all at a temperature of 155°C. Each variation consisted of five samples tested for asphalt properties, including penetration (SNI 2456:2011), ductility (SNI 2432:2011), viscosity (SNI 7729:2011), softening point (SNI 2434:2011), flash point (SNI 2433:2011), and fire point (SNI 2433:2011). The results showed that asphalt properties varied significantly with heating duration (V1–V6), indicating that longer heating had a clear impact on asphalt characteristics. The penetration values obtained for V1 to V6 were 67.17, 64.6, 62.4, 62.2, 58.75, and 49.5, respectively, while the viscosity values were 211 seconds, 206 seconds, 201 seconds, 198 seconds, 193 seconds, and 190 seconds. The softening points were 41.5°C, 43.5°C, 44.5°C, 45°C, 46°C, and 47°C, while the flash points were 318°C, 325°C, 329°C, 330°C, 332°C, and 335°C. The fire points were 330°C, 332°C, 335°C, 340°C, 345°C, and 350°C. The stability values of the mixture increased with heating duration, reaching 1883.5 kg, 2040.5 kg, 2130.2 kg, 2175.0 kg, 2197.4 kg, and 3254.4 kg. Conversely, the flow values decreased, becoming 3.81 mm, 3.05 mm, 2.79 mm, 2.29 mm, 2.16 mm, and 1.91 mm. The average Marshall quotient values for each heating variation were 494.36 kg/mm, 669.45 kg/mm, 762.41 kg/mm, 951.45 kg/mm, 1017.81 kg/mm, and 1235.91 kg/mm. This study can help optimize asphalt heating duration to improve pavement quality and durability. The findings also have the potential to serve as a basis for refining standards and policies in the design and maintenance of more resilient road infrastructure.